Parameterization of indicators for interleaved converters design in photovoltaic applications - Cervellini, María Paula (2022)
The design of power converters for photovoltaic systems is a challenging issue to be addressed. This challenge lies on the need of considering efficiency, thermal and volume requirements at the same time; with the added drawback that these indicators have different behaviors depending on the operation conduction mode and also have opposing effects according to the switching frequency. The complexity increases when interleaved converters are selected, since the relationship among indicators is also affected by the number of phases. Many attempts have beenmade in the literature to address this issue; however, they have all reached partial strategies, focusing on some of the indicators and without taking into consideration the interactions amongthem. In this sense, this work proposes a mechanism to obtain indicators of total efficiency, thermal dissipation in inductors and semiconductors, as well as the volume of magnetic devicesand sinks, as a function of switching frequency and number of phases, for continuous and discontinuous conduction modes. This information is crucial to study the interaction among theperformance indicators, and to determine the most suitable values for the mentioned parameters. In order to show the proposal contribution, the parameters for an interleaved converter thatconnects a photovoltaic array with a direct current bus of 450V are obtained.